Integrated Approach to Delineate Meandering Channel Sands as Potential Stratigraphic Traps - Loo, Sheau Huey; Liaw, Kim Kiat; Lo, Shyh-Zung (International Journal of Engineering and Technology, 2018)
After a half century of exploration, the Malay Basin, a mature hydrocarbon province in SE Asia, faces common challenge that most of the conventional structural reservoirs have been drilled out. As a result, the high-risk stratigraphic traps are considered as viable alternative to boost the dwindling oil reserves. In Y field, the discovery of Early Miocene Group I meander belt channel sands outside the low-relief anticlinal closure is seemed to have made substantial contributions to the later oil production. This sparks the inspiration to develop a practical workflow in visualizing the subtle, yet productive channel systems through integration of multidisciplinary datasets. Results have proven that the co-rendering of multi-attributes could effectively delineate the channel edges and reflection strength of sand bodies. Moreover, through the application of neural network techniques on the extracted waveform shape of seismic attribute, a supervised hierarchical lithofacies map was generated. This can help to create a better linkage between the seismic waveform patterns and lithological details of subsurface features. Wireline log analysis was also performed to verify the hydrocarbon potential of Group I sands. This integrated approach may adopted as a reliable best practice in near-field exploration program, especially in proving up the channel-sand stratigraphic play.